Effect of stem cuttings and IBA concentrations on rooting and percentage success in karonda (Carissa carandas Linn.) under semi-arid ecosystem of western India (Indian Journal of Arid Horticulture, 2018)
Karonda (Carissa carandas Linn.), a xerophytic concentrations of IBA viz. 1000 ppm, 2500 ppm, 5000 ppm  plant can be grown commercially in semi-arid ecosystem of and 7500 ppm were applied on the basal part of each cutting  Western India as protective hedge and block plantation. It is while in case of control, cuttings were untreated. Then these  native to India and popularly known as Bengal currant or treated cuttings were planted in 2 kg capacity poly-bags  Christ's thorn. It is now considered as important arid and semi- containing growing media of Soil, FYM and sand in equal  arid zone fruit crop because of its hardy nature and its proportion. Overhead water sprinkling over the cuttings was  nutritious fruits (Bhavya et al., 2018). Therefore, it can be used done daily in the morning hours. Subsequently the stem  for horticultural plantations in marginal and wastelands, cuttings were carefully maintained and examined during the  owing its hardy nature with wide adaptability to saline sodic experimental period. There were 20 cuttings per treatment per  soils with high pH level (Rai and Misra, 2005). Fruits of replication. The different root and shoot growth parameters  karonda are used for preparation of value added products like were measured after 8th week of planting. Further, success  pickles, chutneys, jelly, candy and Nakal cherry. Nakal percentage and root length were also recorded. The collected  cherry'closely resembles the canned cherry fruits (Rai and data were analyzed statistically and per cent data were  Misra, 2005). According to Dey et al. (2017), the karonda angularly transformed and the critical differences (C.D.) at  fruits are one of the richest sources of iron (39.1 mg/100 g). It 0.05 level of probability were worked out for comparing the  is mainly propagated by seeds, which leads a different degree means.
Keywords: sprinkling; horticultural plantations; wastelands